Development of polychromatic ultraviolet light-emitting diodes based on three-dimensional AlGaN quantum wells. (2nd November 2017) - Kataoka, Ken; Funato, Mitsuru; Kawakami, Yoichi
Abstract: We present polychromatic ultraviolet (UV) spectra from electrically driven light-emitting diodes (LEDs) based on three-dimensional (3D) AlGaN quantum wells (QWs). The LED structure is fabricated on AlN composed of (0001) facets, facets, and vicinal (0001) facets with bunched steps. Although subsequent n-AlGaN growth tends to eliminate step bunching, appropriate design of the growth procedures preserves the 3D structure of AlN even in the LED structure. Because the QWs on the (0001) facets and bunched steps emit different colors, the fabricated LED exhibits polychromatic deep UV emission.